SINTESIS DAN KARAKTERISASI KATALIS Co-Al-MCM-41 - Choirul Anam, ; Ratna Ediati, (Matematika dan Sains, 2011)
MCM-41 is a material that can be used as support for the properties he owned, among other things a uniform pore size and specific surface area is large. In this study has successfully created a catalyst Co-Al-MCM-41 with a hydrothermal method in the form of white powder into the ash-gray with a specific surface area ratio of 20 = 969.01 m2 / g and the ratio 40 = 1078.95 m2 / g and can used as a catalyst in cyclization cytronelal. The results of characterization by XRD, FT-IR and N2 adsorption-desorption showed that the catalyst Co-Al-MCM-41 has the same structure mesopori material MCM-41 is marked by the emergence of characteristic peaks difractogram at 1.8-2.4 ° 2 approximately, 3.5 -4.12 °, 4.31-4.82 °, and 5.64-6.00 °, and the pore size distribution between 30.49-34.09 Å, has a hexagonal shape and uniform particle morphology with average size 1 m. Results desorption nitrogen absorption analysis showed the surface area decreased with the growing amount of Co loading. Catalytic activity of Al-MCM-41 and Co-Al-MCM-41 at cyclization cytronelal reaction influenced by the nature of the acidity of the catalyst, which catalyst has a number of the more Lewis acid and Bronsted acid side has less active and selective nature of the cyclization reaction cytronelal be isopulegol. The highest activity of 81.30% and the highest selectivity of 75.10% for isopulegol shown by the catalyst Co-Al-MCM-41(20) in the solvent toluene. 2 / g and the ratio 40 = 1078.95 m2 / g and can used as a catalyst in cyclization cytronelal. The results of characterization by XRD, FT-IR and N2 adsorption-desorption showed that the catalyst Co-Al-MCM-41 has the same structure mesopori material MCM-41 is marked by the emergence of characteristic peaks difractogram at 1.8-2.4 ° 2 approximately, 3.5 -4.12 °, 4.31-4.82 °, and 5.64-6.00 °, and the pore size distribution between 30.49-34.09 Å, has a hexagonal shape and uniform particle morphology with average size 1 m. Results desorption nitrogen absorption analysis showed the surface area decreased with the growing amount of Co loading. Catalytic activity of Al-MCM-41 and Co-Al-MCM-41 at cyclization cytronelal reaction influenced by the nature of the acidity of the catalyst, which catalyst has a number of the more Lewis acid and Bronsted acid side has less active and selective nature of the cyclization reaction cytronelal be isopulegol. The highest activity of 81.30% and the highest selectivity of 75.10% for isopulegol shown by the catalyst Co-Al-MCM-41(20) in the solvent toluene.